“Unsilencing” the Silence: Unacknowledged silent pieces - Borges Pena, Eder Wilker [UNESP] (OPUS, 2020)
The following work seeks to restore from obscurity three silent pieces of music that predate John Cage’s 4’33” and establish the reasons why they have not been acknowledged as being the first silent pieces. Hence, we present our methodology, analysis, and conclusion based on the motives that led them to musicological oblivion, their relevance in the context of experimental music, and why 4’33” was possible in its zeitgeist.
Quebrando o silêncio: Peças silenciosas não reconhecidas
Keywords: Experimentalism; Humorous music; Silent pieces